Synthesis of aryloxyacetonitriles based on arylboronic acids with 2-bromoacetonitrile. Issue 40 (1st October 2020) - Li, Yingmin; Guo, Mengping; Wen, Yongju; Zhou, Lanjiang; Shen, Xiuli; Kang, Yangping
Graphical abstract: Highlights: A new and efficient protocol for the synthesis of aryloxyacetonitriles. Eco-friendly hydrogen peroxide as oxidant. Metal-free catalyst. First synthetic method of aryloxyacetonitriles using arylboric acids with 2-bromoacetonitrile as reaction substrates. Abstract: A new and efficient protocol for the synthesis of aryloxyacetonitriles based on arylboronic acids with 2-bromoacetonitrile has been developed using eco-friendly hydrogen peroxide as oxidant under metal-free conditions. This method is compatible with arylboronic acid attached sensitive substituent and obtains desired product in moderate to good yield.